Mundane Heterosexualities - Hockey, J. author. aut Link
IX, 206 p.
Keywords: Mundane Heterosexualities provides the reader with a critical overview of feminist thinking on the topic of heterosexuality. It argues that as a social rather than sexual category, heterosexuality can be seen as the organizing principle of our everyday lines.